The impact of macroeconomic determinants on the banking sector development in Nepal (The International Research Journal of Management Science, 2022)
AbstractBackground: The concept of banking sector developmentis multi-dimensional, and it is difficult to establish a singledescription for it because it is an interconnected process thatencompasses increases in the number and quality of financialservices.Objectives: The objective of the study is to examine theimpact of macroeconomic determinants on banking sectordevelopment in Nepal.Methods: The study applied the vector error correction model(VECM) approach technique with economic time series dataranging from 1995 to 2020. The study employed the VECMmodel to avoid the spurious regression problem in theconstruction of contemporary time series econometrics. Theco-integration analysis is used in the study to determine thelong-run equilibrium relationship between the macroeconomicvariable and the banking sector development of the model.Banking sector development is measured by the arithmeticaverage of the normalized values of banking depth, bankingefficiency, and banking stability.Result: This study reveals that per capita GDP and remittanceshave a positive and significant impact on the banking sectordevelopment. Similarly, government expenditure and stockmarket capitalization have positive and statistically significantroles to explain banking sector development in Nepal. Inaddition, it demonstrates that trade openness and inflationhave a marginally negative but insignificant impact on bankingsector development.Conclusion: There is a long-term equilibrium relationshipbetween macroeconomic variables and banking sectordevelopment. Macroeconomic policies and institutional qualityplay an important role in the banking sector development.Implications: For policymakers since it clarifies the significanceof sound macroeconomic policies in the development of thebanking industry while taking into account the quality of theexisting institutional infrastructure.